Semen quality and sperm DNA integrity in city policemen exposed to polluted air in an urban industrial agglomeration - Rubes, Jiri; Sipek, Jaroslav; Kopecka, Vera; Musilova, Petra; Vozdova, Miluse (International journal of hygiene and environmental health, 2021)
BACKGROUND: We examined sperm quality in a cohort of city policemen in Ostrava at the end of a period with high concentrations of air pollutants (winter) and in the same cohort at the end of a relatively low exposure period (summer). METHODS: The study group was comprised of 54 nonsmoking city policemen living and working in Ostrava, Czech Republic. Average daily air-pollutant concentrations recorded by stationary monitoring for 90 days preceding the collection of semen samples were evaluated for different city districts of Ostrava. Standard semen parameters were assessed according to the guidelines of the World Health Organization (2010). The parameters were semen volume, sperm concentration, sperm morphology, sperm motility, acrosome reaction and sperm plasma membrane integrity. Sperm DNA damage was analysed by the sperm chromatin structure assay (SCSA). Sperm motion characteristics were determined by Computer Assisted Semen Analysis (CASA). RESULTS: The concentrations of all monitored pollutants (particulate matter, sulphur dioxide, nitrogen oxides, carbon monoxide, benzo[a]pyrene, benzene) were significantly increased during winter (p < 0.001), except for ozone, the concentration of which was significantly higher during summer. Sperm volume, concentration, % vitality, % sperm morphology (normal form) and % acrosome-intact sperm did not differ significantly between the monitoring periods. The percentages of total motility and progressive motility were significantly higher in March, i.e. at the end of winter (p = 0.001). However, CASA testing showed differences in sperm motion kinetics between spring and autumn samples. In the spring samples, we found a significantly lower % of straightness (p = 0.044) and the length of straight-line path (p = 0.01), while linearity and straight-line velocity were near the borderline value (p = 0.064; p = 0.054, respectively). As compared to summer, high exposure to air pollution during winter significantly increased the extent of sperm chromatin integrity damage (median 22.6 vs. 18.6%) (p = 0.003) and the proportion of immature spermatozoa (median 11.2 vs. 9.9%, p = 0.001). Sperm DNA damage negatively correlated with total motility and progressive motility (r = -0.611, -0.299; p < 0.001). The negative correlation with vitality, normal morphology and acrosome-intact sperm (r = -0.522, -0.550 and -0.511, respectively) was also significant (p < 0.001). CONCLUSION: The examination of the same cohort of city policemen at the end of a period of high air pollution and at the end of relatively low exposure reduced the effects of age, different lifestyles, different occupational exposures, localities and genetic polymorphism on sperm quality impairment associated with air pollution. This study did not demonstrate impaired standard semen parameters in association with exposure. It was shown that sperm chromatin damage and the percentage of immature sperm were highly sensitive to air pollution.
Keywords: sperma; spermie; Humans; Sperm Motility; lidé; Air Pollution; analýza spermatu; DNA; Sperm quality; motilita spermií; Male; DNA fragmentation; Semen Analysis; Semen; Occupational exposure; Spermatozoa; znečištění ovzduší; Air pollution; mužské pohlaví